The Current State of Huntington's Disease Treatment: An Overview of Palliative Care and Symptom Management - Richa Sanyal (International Journal of Cell Biology and Cellular Functions, 2023)
Huntington's disease (HD) is a neurodegenerative ailment that adversely affects the basal ganglia and the cortex of the brain. Although there is no recognized cure for HD, symptomatic relief and therapeutic management of the condition have improved over the course of time. This review paper provides an up-to-date overview of the current treatment options and symptom management strategies utilized in the care of HD patients. Additionally, it highlights the existing research strategies being employed to develop new treatments or technologies for managing the disease. Finally, the paper examines potential future prospects, including gene therapies and other novel approaches to treating HD. The article concludes that while there is still much work to be done to find a cure for HD, current treatment options and research strategies offer hope for a better quality of life for HD patients and their families.
Keywords: ASO therapies; CAG trinucleotides; Huntington’s disease; RNA interference therapy; chorea; stem cell therapy; tetrabenazine; zinc-finger therapies